Living together and Christian ethics - Thatcher, Adrian (Cambridge University Press, 2002)
This book is the first positive, in-depth study of cohabitation outside marriage from a mainstream Christian theological perspective. The book retrieves the traditions of betrothal from the bible and church history, and shows how these can transform Christian attitudes to living together before marriage. It takes issue with theologians who marginalize marriage, and suggests that the recognition of marital values can act as a helpful bridge between Christian teaching and people who are not formally married.